Blendas de amido termoplástico e PBAT processadas com auxílio da pulverização por cisalhamento no estado sólido - Lopes, Henrique Solowej Medeiros (Universidade Federal de São Carlos, 2018)
The use of biodegradable materials arise as a potential alternative for reducing environmental polution. For being found in abundance, low cost, biodegradable and provided from renewable source, starch has been a material of growing researches. Due to its low mechanical properties, high moisture absorption and recrystallization after storage, its use is limited. In this work, thermoplastic starch (TPS) blends with biodegradable polyester Poly(butylene adipate-co-terephthalate) (PBAT) were produced assisted by Solid-State Shear Pulverization (SSSP). The starch was plasticized in the presence of glycerol (25 starch wt%) and water (10 wt%) and processed under various PBAT contents (50, 60, 70 and 80 wt% of TPS). After blending, films were obtained by extrusion. The films were then evaluated for their processability, such as feeding, material handling, visual aspect and water absorption. Their thermomechanical properties were also evaluated by Dynamical-Mechanical Thermal Analysis (DMTA) and tensile strength. Its crystallinity and retrogradation were measured by X-Ray Diffraction (XRD) and its morphology observed by Scanning Electron Microscopy (SEM) and Polarized Optical Microscopy (POM). The SSSP processing step presented greater processability and material handling, with a better visual aspect. For high content starch blends (70 and 80 wt%), techniques showed similar mechanical properties, such as tensile strength, and water absorption. For low starch content (50 and 60wt%), materials produced by conventional extrusion presented higher mechanical properties, such as elongation, and lower water absorption. Both materials showed increased crystallinity over time. It was possible to observe native starch granules in both techniques’ steps, indicating low plasticizing degree.
Processing of thermoplastic starch and PBAT blends assisted by solid-state shear pulverization
Keywords: Amido termoplástico; PBAT; S3P; Blenda; Biodegradável; Thermoplastic starch; SSSP; Blend; Biodegradable; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA